2013
DOI: 10.1246/cl.130656
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of a Liquid-like Spin State in Molecule-based Magnets with Geometric Frustrations

Abstract: We review novel thermodynamic properties of κ-(BEDT-TTF) 2 Cu 2 (CN) 3 and EtMe 3 Sb[Pd(dmit) 2 ] 2 , where BEDT-TTF stands for bisethylenedithiotetrathiafulvalene and dmit stands for 1,3-dithiole-2-thione-4,5-dithiolate unveiled via singlecrystal calorimetry. These compounds are organic dimer-based Mott insulators with a two-dimensional triangular lattice, where electron correlations produce localized radical spins on each molecular dimer. Néel-type magnetic orderings are prohibited by geometric frustrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Thermodynamic measurements are consistent with a mix of gapped and gapless behavior at low temperature [260,[490][491][492][493]. The magnetic susceptibility measured using a torque magnetometer, which cancels impurity Curie contributions, remains paramagnetic to very low temperatures (30 mK) [493].…”
Section: β -Etmesupporting
confidence: 53%
See 1 more Smart Citation
“…Thermodynamic measurements are consistent with a mix of gapped and gapless behavior at low temperature [260,[490][491][492][493]. The magnetic susceptibility measured using a torque magnetometer, which cancels impurity Curie contributions, remains paramagnetic to very low temperatures (30 mK) [493].…”
Section: β -Etmesupporting
confidence: 53%
“…Spin liquid phase. κ-(ET) 2 Cu 2 (CN) 3 (κ-CN) is considered as one of the best candidates for a quantum spin liquid (QSL) [215,260]. As shown in Fig.…”
Section: κ Ctsmentioning
confidence: 99%
“…It is unlikely that such a small entropy reflects a bulk QSL phase and, instead, it was suggested that C ∝ T reflects domain wall fluctuations of a valence-bond glass [89]. Certainly, the rich insights from the specific heat measurements by Yamashita, Nakazawa, and coworkers [26,76] aroused large attention over the past decade and will remain subject of vivid discussions also in the upcoming years.…”
Section: Structural Distortion At the '6k Anomaly' 231 Thermodynamic ...mentioning
confidence: 99%
“…The abovementioned organic candidate compounds were suggested to host a gapless QSL state, based on a finite susceptibility χ(T → 0) > 0 [34,36,39] and non-zero Sommer-feld coefficient observed in specific heat measurements [26,38,39,76]. However, many other Mott-insulating systems with magnetic order or a spin gap are known to date.…”
Section: Introductionmentioning
confidence: 99%
“…13 As a matter of fact, the γ value of the spin liquid systems give similar magnitude as conducting compounds based on BEDT-TTF molecule and other donors/acceptors. 25,26 Although the gapless feature is commonly observed for spin liquid compounds, there still remains a question whether the gapless characters are stable up to high magnetic field as is true in the Fermi liquid systems. The thermal conductivity measurements for κ-(BEDT-TTF) 2 Cu 2 (CN) 3 in the dilution temperature region revealed possibility of tiny gap opening with Δ = 0.016 J/k B 15 and the μSR measurement detected a very weak internal magnetic field at extremely low temperature region.…”
Section: Introductionmentioning
confidence: 99%